Ihdad Bagi Wanita Karir - Syaiful Muda’i (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
The conflict arising from career women and the considerations that may affect the laws of iddah and ihdad can be viewed within the context of the conflicting circumstances they face, which deviate from the original intent of the laws. Considering the need and urgency present, these laws can become more effective for career women and more humane in the millennial era. Meanwhile, emphasizing adornment during the ihdad period for women in their iddah is seen as a means to attract attention from men. In this case, the priority and purpose of ihdad can be eliminated by the need and urgency (emergency situation). Therefore, the law of mediation follows the priority of the law's objective. This means that career women are not subjected to ihdad (it is allowed for them), but they are still required to observe the iddah period. Adorning oneself for career women is a job requirement aimed at preserving their employment so that they can sustain themselves financially. It's important to note that the interpretation and application of these laws can vary within different cultural, religious, and legal contexts. The specific guidelines and practices may differ based on the specific beliefs and rulings of religious scholars or legal authorities in a particular jurisdiction.